2016
DOI: 10.18632/oncotarget.6946
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of SUMO1P3 predicts poor prognosis and promotes tumor growth and metastasis in bladder cancer

Abstract: Bladder cancer is one of the most common malignancies worldwide. Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs that play crucial roles in diverse biological processes. The pseudogene-expressed lncRNA is one major type of lncRNA family. Small ubiquitin-like modifier (SUMO) 1 pseudogene 3, (SUMO1P3) is a novel indentified lncRNA that was previously reported to be up-regulated in gastric cancer. However, we know nothing about the biological function and underlying mechanism of SUMO1P3 in tumor. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 34 publications
(29 reference statements)
1
87
0
Order By: Relevance
“…Recently, the further comprehensive mechanism between H19 and BCa was reported in continuance3435. Our previous researches also identified several lncRNAs, like PVT1 and SUMO1P3, which play oncogenic roles in BCa3637. Therefore, the identification of BCa-associated lncRNAs may provide an opportunity to reveal the mechanism network of cancer pathogenesis in BCa for further targeted treatment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, the further comprehensive mechanism between H19 and BCa was reported in continuance3435. Our previous researches also identified several lncRNAs, like PVT1 and SUMO1P3, which play oncogenic roles in BCa3637. Therefore, the identification of BCa-associated lncRNAs may provide an opportunity to reveal the mechanism network of cancer pathogenesis in BCa for further targeted treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Both of the two experiments were performed as previously reported in Zhan et al 37. The assays were performed in triplicate and the each experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…As expected, knockdown of SPRY4-IT1 decreased the proliferation and migration in bladder cancer cells. 22 …”
Section: Other Cancersmentioning
confidence: 99%
“…Previously, multiple studies reported that in different types of cancer there was abnormal expression of lncRNA, indicating that the same lncRNA may serve different functions in different types of cancer. For instance, a lncRNA named SPRY4 intronic transcript 1 (SPRY4-IT1) was reported to be overexpressed in melanoma, renal cell carcinoma, esophageal squamous cell carcinoma, breast cancer, bladder cancer and glioma, and associated with poor prognosis and promotion of tumor growth (24)(25)(26)(27)(28)(29). Certain studies also demonstrated that SPRY4-IT1 expression was decreased in non-small-cell lung cancer and gastric cancer, and acted with significant antitumor function in these two types of cancer (30,31).…”
Section: Discussionmentioning
confidence: 99%